2018
DOI: 10.1111/add.14189
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, pattern of drinking and all‐cause mortality in Russia, Belarus and Hungary: a retrospective indirect cohort study based on mortality of relatives

Abstract: Drinking frequency is associated positively with mortality among men and women in Russia, Belarus and Hungary. The mortality risk is higher among frequent drinkers who exhibit binge and hazardous drinking patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…However, it must be noted that weekly recommended amounts of alcohol should be spread across several days and not include episodes of heavy alcohol use or "binge drinking", as irregular heavy drinking is associated with a higher risk of ischemic heart disease [79]. This episodic heavy drinking is defined by the World Health Organization as consumption of ≥60 g (approximately ≥6 drinks) per occasion [80] and by the United States National Institute on Alcohol Abuse and Alcoholism [81] as consumption of ≥5 drinks (male) or ≥4 drinks (female) in less than 2 h. While moderate regular drinking is associated with a lower risk of ischemic heart disease compared with abstention [54,82], excessive or binge drinking not only increases the risk of CV events, but also the risk of all-cause mortality [51,83]. Therefore, consumption of moderate amounts of alcohol should be always considered in the context of the Mediterranean lifestyle (moderate quantities of alcohol consumed as part of a meal), as a strategy to promote a more socially responsible consumption, avoiding excessive alcohol intake, often associated with Nordic European, as well as Central and Eastern Europeans and Anglo-Saxon alcohol consumers [10,84].…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be noted that weekly recommended amounts of alcohol should be spread across several days and not include episodes of heavy alcohol use or "binge drinking", as irregular heavy drinking is associated with a higher risk of ischemic heart disease [79]. This episodic heavy drinking is defined by the World Health Organization as consumption of ≥60 g (approximately ≥6 drinks) per occasion [80] and by the United States National Institute on Alcohol Abuse and Alcoholism [81] as consumption of ≥5 drinks (male) or ≥4 drinks (female) in less than 2 h. While moderate regular drinking is associated with a lower risk of ischemic heart disease compared with abstention [54,82], excessive or binge drinking not only increases the risk of CV events, but also the risk of all-cause mortality [51,83]. Therefore, consumption of moderate amounts of alcohol should be always considered in the context of the Mediterranean lifestyle (moderate quantities of alcohol consumed as part of a meal), as a strategy to promote a more socially responsible consumption, avoiding excessive alcohol intake, often associated with Nordic European, as well as Central and Eastern Europeans and Anglo-Saxon alcohol consumers [10,84].…”
Section: Discussionmentioning
confidence: 99%
“…The body of evidence included 60 articles (see Table 1): one Mendelian randomization study, 1 one retrospective cohort study, 16 and 58 prospective cohort studies. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] The evidence included no RCTs.…”
Section: Primary and Secondary Comparisonsmentioning
confidence: 99%
“…There were 35 studies that reported all-cause mortality among men and women combined [6][7][8][9][10][11][12][13][14][15][16]21,25,26,28,31,[34][35][36][37][38][39]45,46,[50][51][52][53][54][55][56][57][58][59][60] ; 26 studies provided results stratified by sex, [2][3][4]9,[11][12][13][15][16][17][18]20,[22][23][24]28,29,32,34,[41]…”
Section: Outcomementioning
confidence: 99%
“…At the same time, Hinote et al (2009) suggested, 'after the collapse of the Soviet state, women are more able to embrace behavioral practices related to alcohol, and many may do so as an overt rejection of traditional Soviet norms and values' (Hinote et al, 2009). Horvat et al (2018) showed that 'drinking frequency is associated positively with mortality among men and women in Russia' (Horvat et al, 2018(Horvat et al, : 1252. Thus, the hypothesis that alcohol consumption has a positive effect on the gender gap in life expectancy remains relevant.…”
Section: The Problem Of the Large Gender Gap In Life E Xpectancy In Rmentioning
confidence: 99%